29th Digital Avionics Systems Conference 2010
DOI: 10.1109/dasc.2010.5655381
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of optimized collision avoidance logic to modeling errors

Abstract: Collision avoidance systems, whether for manned or unmanned aircraft, must reliably prevent collision while minimizing alerts. Deciding what action to execute at a particular instant may be framed as a multiple-objective optimization problem that can be solved offline by computers. Prior work has explored methods of efficiently computing the optimal collision avoidance logic from a probabilistic model of aircraft behavior and a cost function. One potential concern with using a probabilistic model to construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The evaluation simulations use the same intruder random turn rate model with standard deviation σ ψ that was used for value iteration. A robustness study using different models is not presented here, but previous research [13] suggests that this method will offer good performance when evaluated against both a range of noise parameters and structurally different models. The intruder initial position is randomly generated between 800 m and 1500 m from the center point of the encounter area at (500m, 500m) with an initial heading that is within 135 • of the direction from the initial position to the center point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation simulations use the same intruder random turn rate model with standard deviation σ ψ that was used for value iteration. A robustness study using different models is not presented here, but previous research [13] suggests that this method will offer good performance when evaluated against both a range of noise parameters and structurally different models. The intruder initial position is randomly generated between 800 m and 1500 m from the center point of the encounter area at (500m, 500m) with an initial heading that is within 135 • of the direction from the initial position to the center point.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the TRL could be extended to handle variable speed and altitude, but the policy that governs the TRL parameters could be optimized only on the most important dimensions of the model (e.g., the horizontal plane). See [13] for a similar successful example.…”
Section: A Model Assumptionsmentioning
confidence: 99%
“…Finally, X t and h tÀ1 are passed through a sigmoid layer, and c t is passed through a tangent layer. The multiplication of the results of these two layers forms the output h t of the current LSTM module as shown in equation (7). Since they produce the output, these functions are called the output gate of the LSTM module.…”
Section: Lstm Network Structurementioning
confidence: 99%
“…4 Many researchers have been using this model in evaluating the performance of TCAS in new scenarios, 5,6 or studying new collision avoidance algorithms. 7,8 However, the major criticism of this model is that this model assumes pilot behavior is deterministic, that is, the response time delay and acceleration are fixed inspite of the different human pilot and different situation. Through analyzing radar data, researchers have already found that the deterministic pilot behavior model could not adequately describe realistic pilot behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed introduction of each parameter in the simulation model is shown in Table 3. In order to generate a three-aircraft scenario, this paper adopts MIT Lincoln Laboratory's CASSATT to evaluate TCAS multi-aircraft conflict [26][27][28]. At first, we used the model to generate a pairwise conflict between two aircraft.…”
Section: Simulation Modelingmentioning
confidence: 99%